A mechanism for visual orientation may facilitate courtship in a fiddler crab. (March 2015) - Kim, Tae Won; Christy, John H.
Abstract : Some social signals are sexually selected both by female mating preferences and by male–male competition for mates. Studies of the behavioural mechanisms that mediate responses to these signals provide insight into how sexual selection operates. Courting male fiddler crabs, Uca terpsichores, sometimes build large sand structures called hoods at the openings to their burrows. Hoods attract females to males' burrows for mating because they elicit landmark orientation, a behaviour that is selected by predation. Males also orient visually to their own hoods when errors are introduced experimentally into their nonvisual mechanism for path integration. These errors occur naturally when males move far from their burrows to court females or fight neighbours. Here we explored whether courting males also use hoods as visual beacons to the location of their burrow. Crabs that rely on path integration to orient to their burrow keep their lateral axis closely aligned with the bearing home. We therefore measured and compared the distances males moved from their burrows and the maximum deviations between males' body axes and home bearings for males that did and did not build hoods, males that had their hood removed and males that had a hood added to their burrow. Males with hoods did not range further from their burrows than those without hoods, but they exhibited greater maximum deviations between their body axes and the bearings to their burrows. Hoods may facilitate courtship by allowing males to move more freely than when they rely on nonvisual path integration alone. Highlights: Courting male fiddler crabs build sand hoods that attract females for mating. Males use their hood to find their burrow when their nonvisual path map fails. Hoods also allow males to move more freely when courting females at a distance. Multiple modes of sexual and natural selection favour this sexual signal.